2021
DOI: 10.1038/s41598-021-93834-0
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of an innovative gluten-free, low-carbohydrate and high protein-bread enriched with pea protein powder

Abstract: The study aimed to determine the effect of pea protein powder on the pasting behavior and physico-chemical properties including the composition of amino and fatty acids of gluten-free bread with low-carbohydrate content. The control bread recipe was based on buckwheat flour (50 g) and flaxseed flour (50 g) as main flours. Additionally, the improving additives for this control bread such as psyllium husk (4 g), potato fiber (2 g), and guar gum (2 g) were used. The mixture of base flour was supplemented with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…Similarly to our results, Burešová et al [ 20 ] reported that rice bread exhibited a higher cohesiveness value (0.76) compared to chickpea bread (0.58), highlighting the negative effect of chickpea flour addition on cohesiveness. Moreover, decreasing cohesiveness values were also observed when high pea protein powder (almost 20%, flour-based) was added in the buckwheat–flaxseed based GF bread formulations [ 46 ]. Accordingly, the replacement of 25% of RF with the chickpea flours having higher protein content ( Section 3.1 ) determined a decrease of the bread cohesiveness ( Figure 2 ), presumably due to more rigidity of the starch–protein network.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to our results, Burešová et al [ 20 ] reported that rice bread exhibited a higher cohesiveness value (0.76) compared to chickpea bread (0.58), highlighting the negative effect of chickpea flour addition on cohesiveness. Moreover, decreasing cohesiveness values were also observed when high pea protein powder (almost 20%, flour-based) was added in the buckwheat–flaxseed based GF bread formulations [ 46 ]. Accordingly, the replacement of 25% of RF with the chickpea flours having higher protein content ( Section 3.1 ) determined a decrease of the bread cohesiveness ( Figure 2 ), presumably due to more rigidity of the starch–protein network.…”
Section: Resultsmentioning
confidence: 99%
“…Gluten-free bread is usually characterized by high hardness, low elasticity, and low springiness [ 17 ]; thus, it is important to ensure that these parameters are not worsened further. A base recipe for gluten-free bread with a low amount of carbohydrates and a high amount of protein was formulated in a previous work [ 19 ], which was also accepted by consumers. The results of the present study confirmed that the addition of PF did not cause any adverse textural changes in bread.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of PF on the pasting properties of bread were investigated using an RVA-4500 system (Perten Instruments, Macquarie Park, Australia), according to the standard method 22–08 (AACCI, 2000), as described by Wójcik et al [ 19 ]. This analysis was carried out in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations